Study of the phytoestrogen content of goat`s rue (Galaga orientalis), alfalfa (Medicago sativa) and white clover (Trifolium repens) - Saloniemi, Hannu; Kallela, Kaarlo; Saastamoinen, Ilkka (Agricultural Research Centre of Finland, 1993)
Tutkimuksissa selvitettiin Maatalouden tutkimuskeskuksen tutkimusasemilla viljelykokeissa olevien vuohenherneen (Galega orientalis Lam.), sinimailasen (Medicago sativa L.) ja valkoapilan (Trifolium repens L.) kasviestrogeenipitoisuutta. Tutkimuksen mukaan vuohenherne ei aivan vähäisiä määriä lukuunottamatta sisältänyt tunnettuja kasviestrogeeneja. Myöskään biologisissa kokeissa sillä ei ollut estrogeenista vaikutusta. Sinimailasen estrogeeninen teho johtui ilmeisesti kasvin coumestrolista, jota näytteissä oli 34-65 ppm. Kaikkien valkoapilalajikkeiden estrogeenisten isoflavonien ja coumestrolin määrä oli hyvin pieni, eikä se riitä selvittämään biologisessa kokeissa immaturen rotan kohdun painossa todettua lisäystä.

Studies were conducted to determine the phytoestrogen content of goat's rue (Galega orientalis Lam.), alfalfa (Medicago sativa L.) and white clover (Trifolium repens L.), all belonging to the Fabaceae family subjected to test cultivation at research stations of the Agricultural Research Centre of Finland. Apart from some insignificant quantities, goat's rue did not contain any known phytoestrogens. Even in biological Studies it had no estrogenic effect. The estrogenic effect of alfalfa was apparently due to coumestrol, which was discovered in the samples in quantities of 34-65 ppm. All white clover varieties contained very small quantities of estrogenic isoflavones and coumestrol, and they did not explain the increased weight of the immature rat uterus observed in the biological studies.
Keywords: Ka; vuohenherne; sinimailanen; valkoapila; phytoestrogens; goat's rue; alfalfa; white clover